On the estimation of the critical pressure for a closed strictly convex shell with non-canonical shape - Babenko, V. I.; Dunaieska, M. D. (Reports of the National Academy of Sciences of Ukraine, 2016)
An a priori upper bound of the asymptotic value of critical pressure for a closed strictly convex shell with non-canonical shape by its two integral parameters (diameter of the median surface and radius of the ball contained in the shell) is obtained.